Pengaruh Problem-Based Learning terhadap Hasil Belajar Cerita tentang Daerahku Pada Siswa Kelas IV Sekolah Dasar - Hanifatuffida, Azmi; Yatri, Ika (Universitas Negeri Padang, 2024)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the learning outcomes of fourth-grade students of SDN Ciracas 10 on the material